Audit committee characteristics and investors’ stake in Nigerian quoted companies / Olaoye Oladipupo Festus … [et al.] - Festus, Olaoye Oladipupo; Gideon, Akinleye Tayo; Adesodun, Adebayo Isaac; Clement, Olaoye Olatunji (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2020)
Financial scandals that occurred in the early 21st century have put to test the integrity of financial reports that relay the performance of an entity to its investors. The audit committee has been argued in the extant literature as a factor that can put to rest the prevalence of these scandals. Nevertheless, these scandals still recur. This study investigated the nexus between audit committee qualities and investors’ stake in quoted companies in Nigeria. Ex-post facto was adopted as the research design, while the Fixed Effect Panel Analysis and Pairwise Granger Causality Test were used to analyze the data. The results of the Fixed Panel Analysis revealed that the financial expertise, audit committee meetings, numbers of non-executive directors on the audit committee, audit committee size, and the proportion of nonexecutive directors on the board of the selected companies demonstrated an insignificant effect on investors’ stake in the selected quoted companies in the country, while the Panel Granger Causality Test revealed unidirectional causality between earnings per share and proportion of non-executive directors of the company’s board in selected quoted companies in Nigeria. This study concluded that audit committee quality has affect on investors’ stake depending on the qualities adopted by the audit committee. Based on the above, the study recommended among other things, that the management and government should devise internal control mechanisms or strategies that will ensure the suitability of who could act as an independent non executive director to a company.